91 The Effectiveness and Cost-Effectiveness of Spinal Cord Stimulation for Refractory Angina (Rascal Study): A Pilot Randomized Controlled Trial. (3rd June 2016) - Davies, Edward; Eldabe, Sam; Thomson, Simon; Duarte, Rui; Brookes, Moran; deBelder, Mark; Raphael, Jon; Taylor, Rod
Abstract : Introduction: Patients with refractory angina (RA) unsuitable for coronary revascularization experience high levels of hospitalization and poor health-related quality of life. Randomized trials have shown spinal cord stimulation (SCS) to be a promising treatment for chronic stable angina and RA; however, none has compared SCS with usual care (UC). The aim of this pilot study was to address the key uncertainties of conducting a definitive multicenter trial to assess the clinical and cost-effectiveness of SCS in RA patients, i.e., recruitment and retention of patients, burden of outcome measures and our ability to standardize UC in a UK NHS setting. Methods: Patients were recruited from 4 UK sites between January 2011 and June 2014. RA was defined as Class III or IV angina despite optimal anti-angina therapy with angiographically documented coronary artery disease deemed unsuitable for revascularization by the referring cardiologist or cardiothoracic surgeon. All patients had demonstrable ischemia on functional testing and satisfied multidisciplinary assessment for SCS suitability. RA patients deemed suitable were randomized in a 1:1 ratio to SCS plus UC (SCS group) or UC alone (UC group). We sought to assess: recruitment, uptake, and retention of patients; feasibility and acceptability of SCS treatment; the feasibility and acceptability of standardizing UC; and the feasibility and acceptability of the proposed trial outcome measures. Patient outcomes were assessed at baseline (prerandomization) and three and six months postrandomization. Results: We failed to meet our planned recruitment target (45 patients) and randomized 29 patients (15 SCS group, 14 UC group) over a 42-month period across our sites. None of the study participants chose to withdraw following consent and randomization. With exception of two deaths, all completed evaluation at baseline and follow-up. Although not formally powered to compare outcomes either within or between groups, we did see evidence of an improvement in health related quality of life demonstrated by the disease-specific Seattle Angina Questionnaire (SAQ) as well as generic quality of life questionnaires, exercise capacity, and reduction in angina frequency at follow-up in both groups, with a trend towards larger improvements in the SCS group (Figure 1 ). Conclusions: While patient recruitment was found to be challenging, levels of participant retention, outcome completion, and acceptability of SCS therapy were high. Lessons learnt from this pilot study will help develop an appropriately powered trial to detect any meaningful superiority of spinal cord stimulation for RA patients.